2017
DOI: 10.1038/cddis.2017.382
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ZNF503-AS1 promotes RPE differentiation by downregulating ZNF503 expression

Abstract: Long noncoding RNAs (lncRNAs) have important roles in various biological processes. Our previous work has revealed that dedifferentiation of retinal pigment epithelium (RPE) cells contributes to the pathology of age-related macular degeneration (AMD). Herein, we show roles of lncRNAs in RPE differentiation. We used microarray to identify lncRNA expression profiles in human induced pluripotent stem cells (hiPSCs) and hiPSC-derived RPE cells. A total of 217 differentially expressed lncRNAs along with the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 47 publications
1
38
2
Order By: Relevance
“…Despite several studies reported important roles of particular lncRNAs such as ZNF503-AS1 and BANCR in RPE cells through in vitro studies [22,23], none of them have investigated the role of lncRNAs in CNV. The present study profiled lncRNA and mRNA expression in the mouse model of laser-induced CNV by integrated microarray analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite several studies reported important roles of particular lncRNAs such as ZNF503-AS1 and BANCR in RPE cells through in vitro studies [22,23], none of them have investigated the role of lncRNAs in CNV. The present study profiled lncRNA and mRNA expression in the mouse model of laser-induced CNV by integrated microarray analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Among altered lncRNAs in patients with early AMD, RP11-234O6.2 has been demonstrated as having protective effects in the aging RPE model [21]. A few in vitro studies investigated the roles of several certain lncRNAs (such as ZNF503-AS1 and BANCR) in retinal pigment epithelium (RPE) cells [22,23]. Nevertheless, it still remains unclear that the expression profiles, targets, and effects of lncRNAs and their contribution to the pathogenesis of CNV as well as neovascular AMD.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs arise more attention of ophthalmologists since they contribute to the regulation of RPE cells in various aspects (Kutty et al, 2018;Ye, Li & He, 2017;Chen et al, 2017). To date, several lncRNAs have been identified to play important roles in regulating cellular proliferation and apoptosis in RPE cells (Zhou et al, 2015(Zhou et al, , 2018Li et al, 2018d;Yang et al, 2016), such as lncRNA BDNF-AS, nuclear factor-κB (NF-κB) Interacting LncRNA and Metastasis Associated Lung Adenocarcinoma Transcript 1 (MALAT1).…”
Section: Discussionmentioning
confidence: 99%
“…ZNF503-AS1 is regulated by NF-κB which is involved in cellular processes such as inflammation and differentiation of RPE. Targeting both RP-1123406.2 and ZNF503-AS1 is a potential therapeutic strategy for atrophic AMD (Chen et al, 2017a).…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%